Electrical and microstructural properties of microwave sintered SnO2-based varistors - Furtado,P. S. (2012)
An investigation was made of the microstructural and electrical properties of SnO2-based varistors microwave sintered at 1200 ºC, applying a heating rate of 120 ºC/min and treatment times of 10, 20, 30, 40, 50 and 60 min. The system used in this study was (98.95-X) %SnO2.1.0%CoO.0.05%Cr2O3.X%Ta2O5, where X corresponds to 0.05 and 0.065 mol%. Sintering was carried out in a domestic microwave oven (2.45 GHz) fitted for lab use. Silicon carbide was placed in a refractory vessel to form a heating chamber surrounding the sample holder. The pellets were examined by scanning electron microscopy, X-ray diffractometry, direct current measurements and impedance spectroscopy. The parameters of density, medium grain size, coefficient of nonlinearity, breakdown electrical field, leakage current, and height and width of the potential barrier were analyzed.